Pre-Interventional Kynurenine Predicts Medium-Term Outcome after Contrast Media Exposure Due to Coronary Angiography - Christoph Reichetzeder; Fabian Heunisch; Gina von Einem; Oleg Tsuprykov; Karl-Heinz Kellner; Thomas Dschietzig; Axel Kretschmer; Berthold Hocher (Karger Publishers, 2017)
Background/Aims: Contrast induced acute kidney injury (CI-AKI) remains a serious complication of contrast media enhanced procedures like coronary angiography. There is still a lack of established biomarkers that help to identify patients at high risk for short and long-term complications. The aim of the current study was to evaluate plasma kynurenine as a predictive biomarker for CI-AKI and long-term complications, measured by the combined endpoint "major adverse kidney events" (MAKE) up to 120 days after CM application. Methods: In this prospective cohort study 245 patients undergoing coronary angiography were analyzed. Blood samples were obtained at baseline, 24h and 48h after contrast media (CM) application to diagnose CI-AKI. Patients were followed for 120 days for adverse clinical events including death, the need for dialysis, and a doubling of plasma creatinine. Occurrence of any of these events was summarized in the combined endpoint MAKE. Results: Preinterventional plasma kynurenine was not associated with CI-AKI. Patients who later developed MAKE displayed significantly increased preinterventional plasma kynurenine levels (p<0.0001). ROC analysis revealed that preinterventional kynurenine is highly predictive for MAKE (AUC=0.838; p<0.0001). The optimal cutoff was found at ≥3.5 µmol/L Using this cutoff, the Kaplan-Meier estimator demonstrated that concentrations of plasma kynurenine ≥3.5 µmol/L were significantly associated with a higher prevalence of MAKE until follow up (p<0.0001). This association remained significant in multivariate Cox regression models adjusted for relevant factors of long-term renal outcome. Conclusion: Preinterventional plasma kynurenine might serve as a highly predictive biomarker for MAKE up to 120 days after coronary angiography.